Development of Computational Thinking Skill Instruments on Prospective Physics TeachersDevelopment of Computational Thinking Skill Instruments on Prospective Physics Teachers - Edi Daenuri Anwar; Sarwi Sarwi; Ani Rusilowati; Bambang Subali; Wiwi Isnaeni; Budi Naini Mindyarto (International Conference on Science, Education, and Technology, 2023)
Computing thinking is a specialized skill related to computer science. However, nowadays almost everyone is expected to have basic computing skills that are in line with current technological developments. This research aims to develop an instrument for computational thinking skills in physics education at a university level. The Computational Thinking Instrument was designed to include items related to decomposition, pattern recognition, abstraction, and algorithms. The development of the instrument resulted in 14 valid items. The sample for this study consisted of 104 students majoring in physics education at the Department of Physics Education, UIN Walisongo Semarang, Indonesia. The instrument used in this research employed a modified Likert scale. The validity of the instrument was assessed using content validity and construct validity. Content validity was measured using Aiken's index, while construct validity was assessed using Exploratory Factor Analysis (EFA). The reliability estimation using the Cronbach Alpha formula yielded a value of 0.94, indicating that the assessment instrument for students' computational thinking skills in physics education is reliable. The results of the rotated component matrix revealed that the 14 developed items could be divided into only 2 factor.